Энциклопедия рукоделия для супердевочек: издания для досуга / ред. Л. И. Колесова - Колесова Л.И. (1001 ИДЕЯ, 2011)
Экземпляры: ДБ (20130708) / Инвентарный номер: 42517 / Цена: 354.20 / Сис.шифр: 37.248я2 / Авт.знак: Э 68 / ГРНТИ: 75.35 / ББК: 37.248я2